Resveratrol-Based Nanoformulations as an Emerging Therapeutic Strategy for Cancer - Sharifi-Rad, Javad; Quispe, Cristina; Mukazhanova, Zhazira; Knut, Ewa; Turgumbayeva, Aknur; Kipchakbayeva, Aliya; Seitimova, Gulnaz; Mahomoodally, Mohamad Fawzi; Lobine, Devina; Koay, Aaron; Wang, Jinfan; Sheridan, Helen; et al. (Frontiers in Molecular Biosciences, 2021)
Resveratrol is a polyphenolic stilbene derivative present mainly in grapes, and red wine. It is widely known for its antioxidant properties but numerous studies have also indicated anti-inflammatory, and anti-aging abilities and, above that, a great potential in cancer therapy. Regrettably, oral administration of resveratrol has met pharmacokinetic and physicochemical limitations hampering its effects, demanding another method of administration, to ensure its efficiency. The present review explores published data concerning application of resveratrol nano-formulations in cancer therapy, with the use of different types of nano-delivery systems. Mechanisms of action with potential use in cancer therapy, negative effects, and the influence of resveratrol nano-formulations on different types of cancer is taken into account. Finally, potential toxicity of nano-resveratrol is also discussed.